2022
DOI: 10.1016/j.injury.2021.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Measuring socioeconomic outcomes in trauma patients up to one year post-discharge: A systematic review and meta-analysis

Abstract: W ärnberg , Measuring socioeconomic outcomes in trauma patients up to one year post-discharge: A systematic review and meta-analysis, Injury (2021), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 103 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…As being employed positively influences health and well-being, 80 return to work is among the most-studied socioeconomic outcomes in research among trauma patients. 81 A systematic review and meta-analysis comprising 43 studies showed that more than 36% of adult trauma patients had not returned to work during the first year following discharge, 11 reflecting the mental and physical burden among survivors of physical trauma. The average NISS score in our study population was 23 (range 13–29), categorising the participants as severely injured (NISS>15), and most had yet to return to full-time work or study at 18 months postdischarge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As being employed positively influences health and well-being, 80 return to work is among the most-studied socioeconomic outcomes in research among trauma patients. 81 A systematic review and meta-analysis comprising 43 studies showed that more than 36% of adult trauma patients had not returned to work during the first year following discharge, 11 reflecting the mental and physical burden among survivors of physical trauma. The average NISS score in our study population was 23 (range 13–29), categorising the participants as severely injured (NISS>15), and most had yet to return to full-time work or study at 18 months postdischarge.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma survivors frequently sustain mental and physical impairments that significantly affect their quality of life,9 10 and research has shown that more than one-third of trauma patients do not return to work 1 year after injury,11 reflecting the severe injury burden. Furthermore, longitudinal cohort studies conducted during the 3 years following injury have shown that trauma patients report a high prevalence of ongoing problems with pain, anxiety, depression, daily activities and reduced mobility and self-care 12 13…”
Section: Introductionmentioning
confidence: 99%
“…Injury is a global health concern, and the economic burden attributed to the management of patients with trauma haemorrhage is significant; for example, it was estimated that in England the cost of managing haemorrhage after trauma was GBP 168 million per year [ 8 , 9 ]. Despite extensive efforts to improve clinical management and patient outcomes, trauma remains a clinical and socioeconomic issue of major relevance for young people and is becoming a larger issue for the elderly [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One-third of people admitted to hospital following serious injury do not return to work (RTW) within 12 months (David et al, 2022). Those that do, may suffer from physical and mental health problems, including pain, fatigue, anxiety, depression and post-traumatic stress disorder, which threaten work stability (Cancelliere et al, 2016; Kendrick et al, 2017; Vardon-Bounes et al, 2021; Vitturi et al, 2022) and increase health resource use.…”
Section: Introductionmentioning
confidence: 99%